Model Pengolahan Kas UMKM Sampah Organik untuk Pakan Cacing menggunakan Finite State Automata - Aviv Yuniar Rahman; Bagus Setyawan; Feddy Wanditya Setiawan; April Lia Hananto (Jurnal Ilmiah FIFO, 2019)
Financial processing is currently widely used for business purposes. The business includes small and medium businesses. With these small and medium businesses, the system used still uses financial processes manually in its processing. As a result, there are often errors in the calculation process as well as income and expenditure. And not the same as the results of the calculation. In this cash processing application system, it can help small and medium entrepreneurs to calculate large amounts of data. And will reduce the error rate. The application model is designed using Finite State Automata. With this model, it can be seen that the value of the design testing process shows that the first and second designs have smaller processing processes compared to the third design. It can be said that to conduct data processing in a large way the third design is more accurate than the first and second. It is hoped that this application can be applied by other small and medium micro-entrepreneurs, and can assist in carrying out a more efficient financial management process.